2019
DOI: 10.1002/etc.4562
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects induced by chronic gamma irradiation in progeny of adult fish not affecting parental reproductive performance

Abstract: Multigenerational studies have become of great interest in ecotoxicology since the consequence of parental exposure to contaminants on offspring generations was established in situ or in laboratory conditions. The present study mainly examined the chronic effects of external Cs‐137 gamma irradiation exposure at 4 dose rates (control, 0.5, 5, and 50 mGy h–1) on adult zebrafish (F0) exposed for 10 d and their progeny (F1) exposed or unexposed for 4 to 5 d. The main endpoints investigated included parental reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 53 publications
3
16
1
Order By: Relevance
“…Gamma irradiation has often been shown to induce DNA damages in zebrafish larvae at different dose rates, such as 3.3x10 1 µGy/h (Gagnaire et al 2015b) and from 4.16x10 2 to 4.16x10 5 µGy/h (Simon et al 2011). DNA damages also appeared in progeny when parents were exposed to gamma irradiation (Guirandy et al 2019) or when exposure occur during gametogenesis (Hurem et al 2018). However, at 2.4x10 4 µGy/h, DNA damages increased at 1 dpf and decreased at 4 dpf, suggesting that repair mechanisms occurred (Gagnaire et al 2015b).…”
Section: Effects Of Gamma Irradiation On Embryonic Development Dna Damage Ros Production Gene Expression and Muscle Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…Gamma irradiation has often been shown to induce DNA damages in zebrafish larvae at different dose rates, such as 3.3x10 1 µGy/h (Gagnaire et al 2015b) and from 4.16x10 2 to 4.16x10 5 µGy/h (Simon et al 2011). DNA damages also appeared in progeny when parents were exposed to gamma irradiation (Guirandy et al 2019) or when exposure occur during gametogenesis (Hurem et al 2018). However, at 2.4x10 4 µGy/h, DNA damages increased at 1 dpf and decreased at 4 dpf, suggesting that repair mechanisms occurred (Gagnaire et al 2015b).…”
Section: Effects Of Gamma Irradiation On Embryonic Development Dna Damage Ros Production Gene Expression and Muscle Integritymentioning
confidence: 99%
“…The exact same kind of result was already shown for other pollutants, such as endocrine disruptors (Bado-Nilles et al 2014b) and uranium (Gagnaire et al 2015a, Gagnaire et al 2014, Le Guernic et al 2016. However, an increase of ROS basal level was shown in zebrafish progeny when parents were exposed to gamma irradiation (Guirandy et al 2019, Hurem et al 2017a). On the contrary, 4 dpf larvae exposed to 1.34x10 2 and 1.24x10 3 µGy/h showed also an increase of ROS production index, but this was due to an increase of the stimulated level, as shown before for agricultural products (Bado-Nilles et al 2014a).…”
Section: Effects Of Gamma Irradiation On Embryonic Development Dna Damage Ros Production Gene Expression and Muscle Integritymentioning
confidence: 99%
“…In most cases, the effects after gamma irradiation are assessed at specific sensitive stages, such as the embryo-larval stage, because they are considered to be most vulnerable to ionizing radiation (Gagnaire et al, 2015;Hu et al, 2016;Lerebours et al, 2020;Pereira et al, 2011;Praveen Kumar et al, 2017;Simon et al, 2011a). However, focusing on just one sensitive stage of life is not enough to obtain a comprehensive understanding of the effects ofirradiation in fish (Guirandy et al, 2019;Hurem et al, 2017a;. For example, at 50 to 53 mGy h -1 , F1 irradiated and non-irradiated progeny from F0 irradiated zebrafish (Danio rerio) showed 100% mortality, providing an evidence of transmitted effects from parents to progeny and thus the importance of assessing multigeneration studies These dose rates are not environmentally relevant but contribute to the development of the dose-responses relationships necessary for ERA.…”
Section: Introductionmentioning
confidence: 99%
“…. However, multigeneration studies on IR are scarce but they demonstrated that multigenerational exposure can lead to harmful effects and highlights new toxic mechanisms (see Guirandy et al 2019). These studies suggested that IR can induce (i) epigenetic alterations, such as DNA methylation located on gene promoters and enhancers, which can be inherited by future generations and (ii) altered transcriptomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation